FINANCIAL LITERACY, DIGITAL FINANCE AND FINANCIAL INCLUSION AMONG RURAL WOMEN IN KENYA. - AMUGUNE MILDRED KASAYA (Machakos University Press, 2025)
Financial inclusion is a key pillar to global development. Several efforts have been put in place across the globe to improve financial inclusivity levels. Despite the efforts, in Kenya there is a considerable percentage who are yet to be financially included. Rural women make up a majority of those who are financially excluded yet they are important agents for transformational economic change. Several studies have concentrated on individual variables in isolation in relation to financial inclusion. This study sought to jointly analyze the influence of financial literacy and digital finance on financial inclusion among rural women in Kenya. Specifically, it sought to assess the influence of financial literacy on financial inclusion, investigate the role of digital finance on financial inclusion, establish the interaction effect of financial literacy and digital finance on financial inclusion and analyze rural women’s perspectives on financial inclusion among rural women in Kenya. The study was anchored on the Financial Literacy Theory, Social Learning Theory, Diffusion of Innovation Theory and the Vulnerability Theories that helped address the objectives. A descriptive cross-sectional research design was adopted to help gain an understanding on how the independent variables; financial literacy and digital finance influenced financial inclusion among rural women in Kenya at a specific point in time. The target population was rural women in Kenya who were purposively selected from seven regions to represents financial inclusivity in Kenya on a sample of 1000. The standard Global Findex database as well as the FinAccess questionnaires were adopted and modified for collection of primary data. Data was analysed using descriptive statistical analysis, partial least square structural equation model (PLS – SEM) and Chi-square test of Independence. The study revealed that financial literacy with a positive path coefficient of 0.466, explains approximately 21.7% of the variance in financial inclusion, digital finance explains (0.728) approximately 53.0% of the variation while digital literacy (a combination of financial literacy and digital finance) explains up to 56.1% of the variation in financial inclusion among rural women in Kenya. Rural women perspectives were also found to explain about 18.7% of variance in financial inclusion. Further analysis using the Chi-square revealed that there is a statistically significant association between digital financial literacy and financial inclusion among rural women in Kenya (χ2=397.64 >6.635). This study concludes that there is a strong interconnection between financial literacy and digital finance where both play a pivotal role in determining the level of financial inclusion among rural women. It adds that while challenges exist, there are clear opportunities for intervention and improvement and that the success of financial inclusion initiatives will depend on addressing both the knowledge and behavioral gaps identified in this study. The study recommends designing of localized financial literacy programs for understanding of basic financial concepts, enhancing digital infrastructure and accessibility, creation of awareness on financial products and services and creation of targeted interventions that will build trust on digital financial services among rural women in Kenya.